Constructing medieval sexuality - Lochrie, Karma; McCracken, Peggy; Schultz, James A. (James Alfred), 1947- (Medieval cultures ;, 1997)
This collection is the first to be devoted entirely to medieval sexuality informed by current theories of sexuality and gender. It brings together essays from various disciplinary perspectives to consider how the Middle Ages defined, regulated, and represented sexual practices and desires.